A novel, proof-of-concept radiofrequency renal denervation strategy to improve procedural efficiency: 12-month results from the SPYRAL DYSTAL pilot study - Sharp, Andrew S.P.; Kandzari, David E.; Townsend, Raymond R.; Kario, Kazuomi; Mahfoud, Felix; Weber, Michael A.; Schmieder, Roland; Tsioufis, Konstantinos; Böhm, Michael; Choi, James W.; Liu, Minglei; DeBruin, Vanessa; et al. (Cardiovascular Revascularization Medicine, 2024)
Background: Catheter-based renal sympathetic denervation (RDN) reduced blood pressure (BP) in multiple randomized sham-controlled trials of patients with uncontrolled hypertension (HTN). We tested proof-of-concept for a more selective treatment strategy, exclusively targeting these areas to improve the efficiency of the procedure. Methods: The SPYRAL DYSTAL Pilot study was designed to mirror the SPYRAL HTN-OFF MED Pivotal study, enabling comparison with a propensity score adjusted active-control group. Patients were antihypertensive medication-free for one month before undergoing BP assessment. Those with office BP of 150–180/>90 mmHg and with an ambulatory systolic BP of 140–170 mmHg were selected to undergo open label treatment, delivering energy only to the distal main renal arteries and first order branches. Patients from DYSTAL were compared with patients who underwent maximized RF RDN treatment in the prior randomized OFF MED trial at 3 months. After 3 months, patients resumed antihypertensive medications as indicated. Safety and efficacy outcomes were assessed post hoc through 12 months. Results: The SPYRAL DYSTAL Pilot study treated 56 HTN patients. Baseline office systolic BP (OSBP) and 24-h ambulatory systolic BP (ASBP) were similar between DYSTAL and OFF MED patient groups. The number of ablations (32.3 ± 8.0 vs 46.6 ± 15.3, p < 0.001), procedure time (67 ± 21 min vs 99 ± 36 min; p < 0.001), and contrast volume (173 ± 77 cc vs 208 ± 96 cc; p = 0.014) were significantly lower with the simplified treatment strategy. OSBP and ASBP changes compared with baseline were −9.0 and −1.4 mmHg at 3 months, −20.3 and −13.9 mmHg at 6 months, and −20.3 and −16.6 mmHg at 12 months, respectively. During the medication up-titration phase, BP reductions among DYSTAL patients were similar to reductions observed in OFF MED through 12 months, with comparable number of drugs (1.4 and 1.5 medications, respectively (P=NS)). Two adverse events related to guidewire placement were reported. Conclusion: In this pilot study, focusing ablation treatment on the distal main and proximal branch renal arteries was performed, resulting in fewer RF lesions, and reduced contrast volume and procedure time. Whether BP reductions are similar between a selective vs. maximized RDN approach requires further prospective study.
CRIS-Team Scopus Importer:2024-05-03
Keywords: Renal denervation; Uncontrolled hypertension